2014
DOI: 10.1016/j.indcrop.2014.03.039
|View full text |Cite
|
Sign up to set email alerts
|

Esterification of organosolv lignin under supercritical conditions

Abstract: An organosolv lignin, extracted in organic acid media, named Biolignin ™ , was acetylated with acetic anhydride in supercritical carbon dioxide (scC02). The effect of moisture and specific surface of lignin sample, temperature (50, 80, 100, 150 "C), reaction time and the use of a catalyst have been studied using analytical techniques such as FT-IR, quantitative 31 P NMR and Differential Scanning Calorimetry (DSC). The reaction appeared ta be more efficient when a dried organosolv lignin was used (97% Dry Matte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 25 publications
(27 reference statements)
0
49
0
3
Order By: Relevance
“…All lignin samples showed a wide absorption band at 3,400 cm −1 , which is assigned to the O-H stretching vibrations in aromatic and aliphatic O-H groups (Tejado et al, 2007). Bands around 2,930 and 2,840 cm −1 can be assigned to C-H vibrations of CH2 and CH3 groups; while signals between 1,700 and 1,400 cm −1 can be attributed to the aromatic skeletal vibrations (Cachet et al, 2014). The C=C of aromatic skeletal vibrations were reflected by peaks at 1,595 and 1,510 cm −1 (Prado et al, 2016b); these two stretches showed decrease in intensity when compared to unreacted alkaline lignin, indicating the oxidation of lignin at tested conditions.…”
Section: Ftir-atrmentioning
confidence: 96%
“…All lignin samples showed a wide absorption band at 3,400 cm −1 , which is assigned to the O-H stretching vibrations in aromatic and aliphatic O-H groups (Tejado et al, 2007). Bands around 2,930 and 2,840 cm −1 can be assigned to C-H vibrations of CH2 and CH3 groups; while signals between 1,700 and 1,400 cm −1 can be attributed to the aromatic skeletal vibrations (Cachet et al, 2014). The C=C of aromatic skeletal vibrations were reflected by peaks at 1,595 and 1,510 cm −1 (Prado et al, 2016b); these two stretches showed decrease in intensity when compared to unreacted alkaline lignin, indicating the oxidation of lignin at tested conditions.…”
Section: Ftir-atrmentioning
confidence: 96%
“…Thus, the DS was qualitatively and quantitatively analyzed with infrared spectra according to the relative peak intensities at 1732 cm -1 (acetyl C=O stretching band) and 1502 cm -1 (C=C stretching of aromatic skeleton) according to the methodology of previous studies (Fox and McDonald 2010;Cachet et al 2014): DS=A~1732/A~1502. Here, 1502 cm -1 was used as an internal standard peak, as it was the same in all samples.…”
Section: Degree Of Substitutionmentioning
confidence: 99%
“…5, a strongly positive correlation coefficient of 0.93 was obtained. Therefore, even if no precise value of DS was determined by FTIR, the ratio of A~1732/A~1502 can give an indication as to the degree of substitution of hydroxyl groups with butyryl groups in the butyrated LS with reasonable accuracy (Cachet et al 2014). In an effort to optimize the reaction, a variety of variables were investigated, including the choline chloride dosage, reaction temperature, reaction duration, and the mass ratio of butyric anhydride-to-LS.…”
Section: Degree Of Substitutionmentioning
confidence: 99%
“…3, the peaks at 1600, 1510, 1460 and 1423 cm −1 corresponding to aromatic skeleton vibrations, the strong broad band centered at about 3400 cm −1 corresponding to O−H stretching vibration, and the peaks at 2939/2848 cm −1 corresponding to methyl/methylene groups are distinguishable for all the samples [30,31]. So MA did not change the main structure of lignin.…”
Section: Ftir Analysismentioning
confidence: 84%
“…The addition of trioxane which was used as internal standards in order to study the change of the content of functional groups had nearly no influence on the signal of functional groups. For the 1 H NMR spectrum of 12 MA-treated lignin, the integrated area of trioxane (5.4-4.9 ppm) was chosen as reference, the integrated area of ArH (8−6.2 ppm), methoxyl groups (3.5−4.1 ppm), alkyl group (0−2.5 ppm), aliphatic hydroxyl groups (3−3.5 ppm), phenolic hydroxyl groups (9.9−10.1 ppm) and COOH (12−12.6 ppm) [25,26,30,31] were calculated ( Table 2). For the 13 C NMR spectrum of 0.50 h MA-treated lignin, the integrated area of trioxane (98-90 ppm) was chosen as reference, the integration area of methoxyl (50−60 ppm) decreased from 3.08 to 2.69, while the integration of carbonyl (150−170 ppm) increased from 1.02 to 1.33.…”
Section: Nmr Analysismentioning
confidence: 99%